Projeto de redes de fornecimento regenerativas - Souza, Vitor Miranda de (2019)
The strategy of environmental impact minimisation has not been effective enough to revert the damage caused to the environment by production systems; a shift is needed towards promoting environmental benefits. These production systems must also cope with disturbances, while ensuring that their function is fulfilled - a capability known as Resilience - to deploy environmental benefits in the long term. Initiatives in the field of Supply Network Design - a specific type of production system - have focused on improving eco-efficiency, proposing eco-effective networks, or enhancing their Resilience. However, it could not be found in the literature any initiative that merge these three approaches, with a focus on environmental regeneration. This thesis aims to contribute in this direction, proposing a procedure to design supply networks that regenerate the environment as it simultaneously fulfil its function. This procedure is approached as an artefact, and Design Science Research Methodology (DSRM) is used for its development. The scientific progress of Sustainable Design (SD) in the context of Operations Management (OM) is mapped through a holistic literature review, based in the ProKnow-C - a methodology to perform bibliometrics and systemic analysis. The Regenerative Supply Network is characterised through the concepts of transdisciplinarity, eco-effectiveness, eco-efficiency and resilience. A definition for the RSND process is proposed, and the RSND procedure is designed, consisting of four stages: (i) description of the network surroundings and identification of a regenerative purpose; (ii) redesign of outputs, inputs and transformation processes; (iii) system conceptualisation, where interactions are depicted using the SocioTechnical and the Socio-Ecological System views, and resilience principles are addressed. (iv), the network environmental and economic performance are optimised, and resilience is quantitatively checked using the Ecosystem Network Analysis. The activities of Demonstration and Evaluation are described in Chapter Four, where the RSND procedure is used to design a household waste management network which regenerates the environment. The regenerative purpose was identified after scrutiny of the Norte Pioneiro region. Twenty-three sites degraded from improper waste disposal were identified; the primary purpose of the waste management network is to regenerate these sites into solar farms, recreational parks or reforested areas. Inputs are identified and outputs are redefined, according to waste recovery options of recyclables sorting, aerobic composting, anaerobic digestion and gasification. Two models were developed: first, a system dynamics model to forecast waste generation, disposal and collection for a 21-year period (2018-2038). Second, a Multi-Scenario, Multi-Period, Multi-Objective, Mixed Integer Linear Programming (MS-MP-MO-MILP) model was developed to solve the capacitated facility location-allocation problem, producing network configurations through two optimisation strategies: maximisation of profit and maximisation of net greenhouse gas (GHG) savings. Economic, environmental and social performance of the solutions obtained for each of the four scenarios are presented and discussed. The main contribution of this research is to show the potential of supply networks to contribute with the regeneration of ecosystems inthe long term, with a sustainable performance in the three dimensions. Limitations and future research are also presented.